2013
DOI: 10.1021/jf304223a
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Locked Nucleic Acid Real-Time Polymerase Chain Reaction Assay for the Detection of Pinus armandii in Mixed Species Pine Nut Samples Associated with Dysgeusia

Abstract: Recent work has shown that the presence of the species Pinus armandii , even when occurring as species mixtures of pine nuts, is correlated with taste disturbance (dysgeusia), also referred to as "pine mouth". Because of this known possibility of pine nut mixtures, a need was identified for a rapid streamlined assay to detect the presence of this species in the presence of other types of pine nuts. A locked nucleic acid probe was employed in a real-time polymerase chain reaction (RT-PCR) format to detect a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…For example if a region that distinguishes important species based on the size of DNA fragments can be identified and validated, this method could be used without sequencing, thus creating a rapid low cost approach to species identification. In the absence of suitable indels, other variable regions in closely related species can be targeted for either PCR, real-time PCR or other sequence based identification methods 40 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example if a region that distinguishes important species based on the size of DNA fragments can be identified and validated, this method could be used without sequencing, thus creating a rapid low cost approach to species identification. In the absence of suitable indels, other variable regions in closely related species can be targeted for either PCR, real-time PCR or other sequence based identification methods 40 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, in 2013 Handy et al . used a large chloroplast dataset to design a species-specific assay to differentiate Pinus armandii , which causes a taste disturbance known as dysgeusia 40 , from other species that do not.…”
Section: Introductionmentioning
confidence: 99%
“…This subject was affected by PNS after ingesting pine nuts from Pinus sibirica , which have previously not been associated with PNS [1, 7,8]. However, recent reports of taste disturbances from samples containing nuts from a mixture of Pinus sibirica and Pinus armandii have been reported [2,9,10]. As a study based on a single individual, is it intended to be hypothesis-generating research with limited generalizability.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies of PNS have been reported [3–5], and one study has described the symptoms of pine nut-related dysgeusia in a total of six subjects [6]. A single species of pine nuts ( Pinus armandii ) has previously been associated with this syndrome [1,7,8], although recent studies have reported taste disturbances from samples containing nuts from a mixture of different Pinus species [2,9,10]. However, the syndrome occurs in only a small fraction of individuals who consume pine nuts, and efforts to identify a common trigger or medical cause responsible for the occurrence of PNS have not been successful [4].…”
Section: Introductionmentioning
confidence: 99%
“…After much chemical testing of consumer complaints, the FDA CFSAN could not determine the cause. A DNA-based approach was applied to determine whether or not a species substitution, Pinus armandii Franch., Pinaceae, was causing this effect [10,11]. Traditional DNA barcoding regions (i.e., matK, rbcL, and ITS2) were not useful in identifying these pines [10]; instead a diagnostic region, ycf1, was targeted from 33 Pinus chloroplast genome comparison and was used to differentiate P. armandii from closely related species using a specific real-time polymerase chain reaction assay [11].…”
mentioning
confidence: 99%